Voice User Interface Design Moving from GUI to Mixed Modal Interaction - Dasgupta, Ritwik (Apress, 2018)
Design and implement voice user interfaces. This guide to VUI helps you make decisions as you deal with the challenges of moving from a GUI world to mixed-modal interactions with GUI and VUI. The way we interact with devices is changing rapidly and this book gives you a close view across major companies via real-world applications and case studies. Voice User Interface Design provides an explanation of the principles of VUI design. The book covers the design phase, with clear explanations and demonstrations of each design principle through examples of multi-modal interactions (GUI plus VUI) and how they differ from pure VUI. The book also differentiates principles of VUI related to chat-based bot interaction models. By the end of the book you will have a vision of the future, imagining new user-oriented scenarios and new avenues, which until now were untouched. What You'll Learn: Implement and adhere to each design principle Understand how VUI differs from other interaction models Work in the current VUI landscape.